Embedded robotics : mobile robot design and applications with embedded systems - Bräunl, Thomas, ....- (Heidelberg : Springer, 2006)
This book presents a unique combination of mobile robots and embedded systems, from introductory to intermediate level. It is structured in three parts, dealing with embedded systems (hardware and software design, actuators, sensors, PID control, multitasking), mobile robot design (driving, balancing, walking, and flying robots), and mobile robot applications (mapping, robot soccer, genetic algorithms, neural networks, behavior-based systems, and simulation). The book is written as a text for courses in computer science, computer engineering, IT, electronic engineering, and mechatronics, as well as a guide for robot hobbyists and researchers.
Keywords: Embedded computer systems -- Design and construction; Mobiele robots; Mobile robots; Robots -- Control systems